Association between coexisting physical, cognitive, and social frailty and sarcopenia in patients undergoing maintenance hemodialysis - Chen, Luchen; Fang, Yanyu; Dong, Yongze; Zhao, Mengjiao; Yao, Shiyan; Zhong, Qi; Wang, Liying; Song, Haixin; Ma, Guannan; Shen, Huajuan (Frontiers in Medicine, 2025)
ObjectivesTo investigate the influencing factors of coexisting physical, cognitive, and social frailty in MHD patients and explore its association with sarcopenia, in order to provide a reference for developing comprehensive intervention strategies targeting multidimensional frailty.MethodsA convenience sample of MHD patients receiving treatment at the hemodialysis centers of two general hospitals in Hangzhou from July to August 2025 was enrolled. Data were collected using a general information questionnaire, Fried Frailty Phenotype Scale, Social Frailty Scale, Mini-Mental State Examination (MMSE), Modified Quantitative Subjective Global Assessment (MQSGA), Self-Rating Depression Scale (SDS), Social Support Rating Scale (SSRS), and International Physical Activity Questionnaire-Short Form (IPAQ-SF). Pearson correlation analysis and binary logistic regression were used to examine the co-occurrence of physical, cognitive, and social frailty and its association with sarcopenia.ResultsA total of 336 questionnaires were distributed and 325 valid responses were collected. Among the 325 MHD patients, the proportions of individuals with frailty in 0, 1, 2, and 3 domains were 60.0% (n = 195), 15.4% (n = 50), 32.0% (n = 104), and 11.1% (n = 36), respectively. The overall prevalence of sarcopenia was 16.0% (n = 52), and a significant positive correlation was observed between sarcopenia and multidimensional frailty (r = 0.488, P < 0.001). Logistic regression analysis identified prealbumin level, social support, age, SGA score, and sarcopenia as significant predictors of coexisting physical, cognitive, and social frailty in MHD patients (P < 0.05). After controlling for potential confounders, sarcopenia remained significantly associated with multidimensional frailty (P < 0.05).ConclusionApproximately 11.1% of MHD patients experience coexisting physical, cognitive, and social frailty. Sarcopenia is significantly associated with this multidimensional frailty. Early identification and intervention targeting sarcopenia and its related factors may help prevent or mitigate frailty in MHD patients.